ANALYSIS OF INVESTMENT FEASIBILITY AND SENSITIVITY ANALYSIS FOR THE XYZ GEOTHERMAL POWER PLANT (GPP) DEVELOPMENT PROJECT - Darussalam Darussalam; Irni Yunita (CV. Radja Publika, 2025)
Currently, the electricity system of North Sulawesi Province is supplied by power plants including Geothermal Power Plant (GPP), Coal-fired Power Plant (CFPP), Hydroelectric Power Plant (HPP), Solar Power Plant (SPP), Diesel Power Plant (DPP), and Gas Turbine Power Plant (GTPP) with a total installed capacity of 589 MW. The Net Capacity (NC) of this system is approximately 492 MW and the Net Supply Capacity (SC) is around 462 MW, resulting in a gap between installed capacity, NC, and SC Over the past few years, the electricity sales growth in North Sulawesi Province has been quite high, around 7.8% based on sales data from 2011-2020, and is projected to continue growing. Additionally, it is expected that the Energy Mix from New and Renewable Energy sources should reach 23% by 2025, thus the development of new power plants from New and Renewable Energy sources can contribute to achieving this Energy Mix. This research is conducted as a further study regarding the feasibility of investing in the development of XYZ Geothermal Power Plant to provide added value for the company. The research method employed is quantitative descriptive method, which involves calculating the Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), Discounted Payback Period (PP), and Sensitivity Analysis (SA). The results show that the investment will be feasible if the capital source for the investment comes from corporate loans for the upstream sector and soft loans for the downstream sector of development, resulting in an NPV of 2,241 thousand USD, an IRR of 11.11%, a PI of 1.01, and a PP of 24 years. Furthermore, the analysis shows that the decision on the capital source is important, as it affects feasibility, and loan variables such as the interest rate in corporate loans and repayment years in soft loans are important factors to consider in increasing economic feasibility. On the other hand, if the best scenario is chosen—decreasing cost variables and increasing both the electricity tariff and capacity factor by 10% from the base scenario—it can result in higher economic feasibility. Moreover, the electricity tariff, capacity factor, production well cost, and power plant cost have the greatest impact on feasibility. Therefore, it is important to strive for the maximum value of the electricity tariff and capacity factor, while minimizing production well and power plant costs as efficiently as possible.